Impact of the 7/14/2016 Nice terrorist attack on pediatric emergency department visits thanks to syndromic surveillance: a descriptive study - Fernandez, Arnaud; Meurice, Laure; Franke, Florian; Vuillermoz, Cecile; Gindt, Morgane; Askenazy, Florence; Vandentorren, Stéphanie (Frontiers in Public Health, 2023)
Study the impact of 14 th July 2016 Nice terrorist attack on Pediatric Emergency Department (PED) visits by youth under 18 years of age.PED visits diagnoses (ICD10) were clustered and analyzed based on retrospective data from the syndromic surveillance system of the Children's university hospital of Nice (Southern France). The studied period ranges from 2013 to 2019, i.e., three years before and after the terrorist attack of 14 th July 2016.Among 416,191 PED visits, the number of visits for stress in 4-17 years old appeared to increase in the three years after the attack compared to the three years before, particularly in September 2016 (acute effect) with 11 visits compared to an average of 2.3 visits per month from September 2013 to 2016 (p=0.001827). In September 2017, we noticed 21 visits compared to an average of 4.8 visits per month during the following period (2013 to 2019). In 2017, PED visits for stress among 4-17 year olds were higher in comparison to the other years of the study: 107 visits compared to an annual average of 57.To our knowledge, this is the first study of the use of the pediatric care system before and after a terrorist attack involving syndromic surveillance. This suggests acute and long-term effects of the terrorist attack on PED use by youth for mental health issues. Further studies of the pediatric care system involving syndromic surveillance are needed in the context of mass violent events, such as terrorist attacks.